Characteristics and Learning Models of the 21st Century - Riska Wulandari (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2021)
21st-century learning is oriented toward student-centered learning. 21st-century learning is learning that provides 21st-century skills to students, known as 4Cs which includes Critical thinking and problem-solving skills, Communication, Collaboration, and Creativity and innovation. This has become an important issue that needs to be considered, studied, and developed by teachers in learning activities as an effort to face the challenges and demands of 21st-century learning. Characteristics of 21st-century learning need to be recognized and the learning models applied in the learning process needs to lead to the demands of 21st-century learning. This article aims to provide insight into the characteristics and learning models of the 21st century. Data collection was carried out using the literature study method, which examining various relevant references. The characteristics of 21st-century learning are integrative, holistic, scientific, contextual, thematic, effective, collaborative, and student-centered. Meanwhile, 21st-century learning models include Discovery Learning, Cooperative Learning, Collaborative Learning, Contextual Learning, Problem Based Learning, and Project-Based Learning.